Role of transient receptor potential ankyrin 1 receptors in rodent models of meningeal nociception – Experiments in vitro. (15th December 2016) - Denner, A.C.; Vogler, B.; Messlinger, K.; De Col, R.
Abstract: Background: The TRP channel ankyrin type 1 (TRPA1) is a nonselective cation channel known to be activated by environmental irritants, cold and endogenous mediators of inflammation. Activation of TRPA1 in trigeminal afferents innervating meningeal structures has recently been suggested to be involved in the generation of headaches. Methods: Two in vitro models of meningeal nociception were employed using the hemisected rodent head preparation, (1) recording of single meningeal afferents and (2) release of calcitonin gene‐related peptide (CGRP) from the cranial dura mater. The role of TRPA1 was examined using the TRPA1 agonists acrolein and mustard oil (MO). BCTC, an inhibitor of TRP vanilloid type 1 receptor channels (TRPV1), and the TRPA1 inhibitor HC030031 as well as mice with genetically deleted TRPA1 and TRPV1 proteins, were used to differentiate between effects. Results: Acrolein did not cause discharge activity in meningeal Aδ‐ or C‐fibres but increased the electrical activation threshold. Acrolein was also effective in releasing CGRP from the dura of TRPV1 −/− but not of TRPA1 −/− mice. MO increased the discharge activity of afferent fibres from rat as well as C57 wild‐type and TRPA1 −/− but not TRPV1 −/− mice. The effect was higher in C57 compared to TRPA1 −/− mice. Conclusion: Sole TRPA1 receptor channel activation releases CGRP and increases the activation threshold of meningeal afferents but does not generate propagated activity, and so would be capable of causing local effects like vasodilatation but not pain generation. In contrast, combined TRPA1 and TRPV1 activation may be rather pronociceptive supporting headache generation. Significance: Sole activation of TRPA1 receptor channels increases the activation threshold but does not cause propagated action potentials in meningeal afferents. TRPA1 agonists cause CGRP release from rodent dura mater. Peripheral TRPA1 receptors may have a pronociceptive function in trigeminal nociception only in combination with TRPV1.